High pressure/high temperature multiphase simulations of dodecane injection to nitrogen: Application on ECN Spray-A. (1st September 2020) - Koukouvinis, Phoevos; Vidal-Roncero, Alvaro; Rodriguez, Carlos; Gavaises, Manolis; Pickett, Lyle
Graphical abstract: Highlights: Real-fluid thermodynamics of fuel injection to nitrogen. log10 (p)-T tabulation is proposed; high accuracy/minimum computational cost. Properties based on NIST-Refprop. Liquid identification using advanced models (PC-SAFT). Baroclinic torque and compressibility effects are driving jet break-up. Abstract: The present work investigates the complex phenomena associated with pressure/high temperature dodecane injection for the Engine Combustion Network (ECN) Spray-A case, employing more elaborate thermodynamic closures, to avoid well known deficiencies concerning density and speed of sound prediction using traditional cubic models. A tabulated thermodynamic approach is proposed here, based on log10 ( p )- T tables, providing very high accuracy across a large range of pressures, spanning from 0 to 2500 bar, with only a small number of interpolation points. The tabulation approach is directly extensible to any thermodynamic model, existing or to be developed in the future. Here NIST REFPROP properties are used, combined with PC-SAFT Vapor-Liquid-Equilibrium to identify the liquid in mixtures penetration, hence avoiding the use of an arbitrary threshold for mass fraction. Identified liquid and vapour penetration are compared against experimental data from the ECN database showing a good agreement, within approximately 3–8% for axial penetration of liquid, 2% for vapor axial penetration and within experimental uncertainty for radial distribution of mass fraction. Analysis of the vortex evolution indicates that driving mechanisms behind the jet break-up are vortex tilting/stretching, then baroclinic torque, leading to Rayleigh-Taylor instabilities, closely followed by vortex dilation and finally viscous effects.